Challenges and opportunities for biogeography—What can we still learn from von Humboldt?. (19th June 2019) - Schrodt, Franziska; Santos, Maria J.; Bailey, Joseph J.; Field, Richard
Abstract: Alexander von Humboldt was arguably the most influential scientist of his day. Although his fame has since lessened relative to some of his contemporaries, we argue that his influence remains strong—mainly because his approach to science inspired others and was instrumental in furthering other scientific disciplines (such as evolution, through Darwin, and conservation science, through Muir)—and that he changed the way that large areas of science are done and communicated. Indeed, he has been called the father of a range of fields, including environmental science, earth system science, plant geography, ecology and conservation. His approach was characterized by making connections between non‐living and living nature (including humans), based on interdisciplinary thinking and informed by large amounts of data from systematic, accurate measurements in a geographical framework. Although his approach largely lacked an evolutionary perspective, he was fundamental to creating the circumstances for Darwin and Wallace to advance evolutionary science. He devoted considerable effort illustrating, communicating and popularizing science, centred on the excitement of pure science. In biogeography, his influence remains strong, including in relating climate to species distributions (e.g. biomes and latitudinal and elevational gradients) and in the use of remote sensing and species distribution modelling in macroecology. However, some key aspects of his approach have faded, particularly as science fragmented into specific disciplines and became more reductionist. We argue that asking questions in a more Humboldtian way is important for addressing current global challenges. This is well‐exemplified by researching links between geodiversity and biodiversity. Progress on this can be made by (a) systematic data collection to improve our knowledge of biodiversity and geodiversity around the world; (b) improving our understanding of the linkages between biodiversity and geodiversity; and (c) developing our understanding of the interactions of geological, biological, ecological, environmental and evolutionary processes in biogeography.